Transcatheter Arterial Chemo Infusion/TACI for Breast Cancer Treatment: A Case Series - Bagaswoto Poedjomartono; Alan Anderson Bangun; Rifki Bachtiar (Indonesian Journal of Cancer, 2022)
Introduction:  Locally advanced breast cancer (LABC) is a large breast tumor with infiltration to surrounding muscle, skin, and lymph nodes, and sometimes followed by inflammatory breast cancer, a rapidly growing cancer that shows a swollen red lump on the skin. Transcatheter intraarterial chemo infusion (TACI) is considered a palliative therapy for inoperable cancer. This case report shows the qualitative results of TACI on LABC in three patients. Case Presentation: Three female patients with LABC were diagnosed and treated at Dr. Sardjito General Hospital Yogyakarta over three years (2014–2016). The age ranged from 48 to 62 years, with a mean age of 56 years. Clinical features include lumps in breasts, soft tissue swelling, ulcers, dimpling of breast skin, nipple discharge, and pain sensation in the breast area. The three patients underwent the TACI procedure. Therapeutic response was evaluated by observing the clinical morphology of the lesions. Conclusions: TACI showed potency as an efficient and effective alternative palliative therapy in the three LABC cases presented. However, further study is needed to inspect TACI’s efficacy and adverse effects in breast cancer cases to be used as evidence-based medicine.